2012
DOI: 10.1038/sc.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

Maximum voluntary ventilation as a sensitive measure to monitor the ventilatory function in cervical spondylotic myelopathy

Abstract: Study design: A prospective clinical cohort study. Objectives: To test if maximum voluntary ventilation (MVV), which is currently underutilized in diseases, serves for assessing subclinical ventilatory impairment in cervical spondylotic myelopathy (CSM). Setting: Kochi Medical School, Japan. Methods: We studied ventilatory function in 49 CSM patients and 20 age-and sex-matched control patients with either lumbar stenosis or lower limb osteoarthritis. All patients underwent ventilatory function studies consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In our study, there was no data regarding the pre- and post-operative patients' respiratory function. Previous study showed that MVV% was significantly correlated with postoperative recovery of the JOA score 7 ) . Unsatisfactory post-operative recovery, including impaired recovery of respiratory function, might be related to the early death in the S group.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our study, there was no data regarding the pre- and post-operative patients' respiratory function. Previous study showed that MVV% was significantly correlated with postoperative recovery of the JOA score 7 ) . Unsatisfactory post-operative recovery, including impaired recovery of respiratory function, might be related to the early death in the S group.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies demonstrated that cervical myelopathy impaired respiratory function 6-8 ) . Nomura et al reported that forced vital capacity%, peak flow rate, and maximum voluntary ventilation (MVV)% in patients with cervical myelopathy was smaller than those in normal controls 6 , 7 ) . Toyoda et al found that expiratory flow was impaired in patients with cervical myelopathy 8 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, respiratory dysfunction in chronically progressive cervical myelopathy is often subtle and subclinical, and respiratory problems rarely become the main symptoms. There are several reports showing that pulmonary function (especially VC) decreases due to cervical myelopathy including OPLL, and some show improvement in pulmonary function after cervical spine surgery (Table ). However, the preoperative %VCs of patients with chronic cervical myelopathy in these reports were as mild as 65.0%‐97.9%, whereas the %VC of our patient was reduced to 39.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In age less than 18 years, it is mainly seen in adolescents suffering from psychiatric disorders and substance abuse [6,7]. In children, it is rarely described [6][7][8], even though extradural cerebellar haematoma [9], parenchymal cerebellar haematoma [9], and acute hydrocephalus [10,11] secondary to any cause have been described in single case reports. We present here a very unique case of a 12-year-old child with neurogenic pulmonary oedema (NPE) and takotsubo cardiomyopathy (TCM) syndrome after surgery for recurrent medulloblastoma.…”
Section: Introductionmentioning
confidence: 99%